Comparison between Open Reduction and Internal Fixation and Minimally Invasive Plate Osteosynthesis for Treatment of Distal Tibia Fractures - Kiriwichian, MD, Nuttaphan (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To compare the results of distal tibia fractures treated by open reduction and internal fixation (ORIF) with minimally invasive plate osteosynthesis (MIPO). Methods: A prospective randomized controlled study of 36 patients with distal tibia fractures (Type A, AO/OTA classification) in Nakhonpathom Hospital from May, 2011 to February, 2013. These patients were diagnosed as closed fracture or open fracture grade I by Gustilo classification. Twenty one were treated by ORIF and fifteen were treated by MIPO using distal tibia locking plate. The operating time, bone union time, rates of superficial infection, rates of malunion and delayed union, and functional outcome according to Teeny and Wiss criteria were analyzed at a 6-month follow-up. Results: Operating time, bone union time, functional outcome, rates of superficial infection were not significantly different between both groups. No malunion and delayed union were observed in either group. Conclusion: The results of distal tibia fractures treated by ORIF with MIPO were not significantly different